Lecture assessment system (login module and manage user module) - Ibrahim, Noraini (2003)
Information Technology Centre (ITC), KUiTTHO has taken an initiative to integrate all their systems into Total Campus Management System (TCMS). Unfortunately, student assessment is not running well. KUiTTHO personnel cannot monitor students' and lecturers' progress and performance closely. Besides that, the lecturers cannot get the exact amount of student list. Therefore, the students do not have any marks and grade. It only realized at the end of academic semester. Thus, an electronic student assessment system needs to be developed to overcome this issue. Lecture Assessment System (LAS) is suggested to make students assessment management going smoothly. This technical writing will cover from planning phase until the development of prototype system. This web-based system is developed according to V-Shape model as software process and MIL-STD-498 standard for document standard.